“Our Wholesome World Doesn’t Want the World of Diseases…”. About Pain and Suffering in the Light of Wojciech Tochman’s reportages - Popławska, Joanna (Starość i młodość w literaturze i kulturze, 2016)
The article presents considerations on the staggering picture of the world and tragedies of ordinarypeople which are depicted in the works of the most eminent contemporary reporter — Wojciech Tochman.He is the author whose texts abound in suffering and loneliness of a single man, which bring chaosto the orderly life of a reader. The analysed reportages are about the people who are unable to talk ontheir own about everyday distress due to their rare disfunctions. The text will be an attempt to draw theboundaries of human suffering. Moreover, it will also seek an answer to the questions whether there existssocial approval consent for suffering these days or whether the illness discourse still encounters lack ofacceptance. The starting point for the analysis will be the early works of Wojciech Tochman included inthe following publications: Schodów się nie pali and Wściekły Pies.